ANALISIS PERUBAHAN LUAS RUANG TERBUKA HIJAU PUBLIK DAN PRIVAT DI KOTA JAMBI - ika - Tianingsih; Yudi Antomi (JURUSAN GEOGRAFI FIS UNP, 2021)
This research was conducted to identify changes in the area of ​​public and private green open space in Jambi City and to identify the factors that influence changes in the area of ​​green open space. This type of research is descriptive quantitative. The research was conducted in Jambi City, and was conducted from June to September 2020. Data collection techniques were obtained through observation and documentation. Data amalisis technique is obtained through spatial and descriptive analysis. The results showed that: (1) In the 2015-2019 period, the area of ​​public Green Open Space (RTH) in Jambi City decreased, which decreased by 2,223.23 hectares from the original 2015 amounting to 10,167.67 hectares to 7,937.44 hectares in 2019 and the area of ​​private green open space in 2015 has increased from an area of ​​6,983.74 hectares to 9,206.97 hectares in 2019; (2) the factors that influence the change in the area of ​​public green open space are health facilities, educational facilities, and economic facilities, while the factor affecting the change in the area of ​​private green open space is population density.